(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
Through a hermeneutical approach, this paper states that personal identity overcomes the aporetic of time when built as a fictional narrative. First, it proposes that the fictional narrative is inscribed in the mimesis circle. Secondly, that imagination is the faculty that creates the meaning of personal identity as fictional narrative. Thirdly, that it is the imagination that establishes the relation among fictional narrative, semantic innovation, and personal identity. Fourthly, that personal identity as fictional narrative stresses the importance of the narrative, which creates itself as a generator of meanings.